Hotspots of missense mutation identify neurodevelopmental disorder genes and functional domains - Geisheker, Madeleine R; Heymann, Gabriel; Wang, Tianyun; Coe, Bradley P; Turner, Tychele N; Stessman, Holly A F; Hoekzema, Kendra; Kvarnung, Malin; Shaw, Marie; Friend, Kathryn; Liebelt, Jan; Barnett, Christopher; et al. (Nature neuroscience, 2017)
Although de novo missense mutations have been predicted to account for more cases of autism than gene-truncating mutations, most research has focused on the latter. We identified the properties of de novo missense mutations in patients with neurodevelopmental disorders (NDDs) and highlight 35 genes with excess missense mutations. Additionally, 40 amino acid sites were recurrently mutated in 36 genes, and targeted sequencing of 20 sites in 17,688 patients with NDD identified 21 new patients with identical missense mutations. One recurrent site substitution (p.A636T) occurs in a glutamate receptor subunit, GRIA1. This same amino acid substitution in the homologous but distinct mouse glutamate receptor subunit Grid2 is associated with Lurcher ataxia. Phenotypic follow-up in five individuals with GRIA1 mutations shows evidence of specific learning disabilities and autism. Overall, we find significant clustering of de novo mutations in 200 genes, highlighting specific functional domains and synaptic candidate genes important in NDD pathology.
Keywords: sekvence aminokyselin; lidé; Autistic Disorder; Receptors, Glutamate; Female; glutamátové receptory; Mutation, Missense; Humans; mužské pohlaví; genetická predispozice k nemoci; autistická porucha; ženské pohlaví; Exome; missense mutace; Male; exom; Genetic Predisposition to Disease; Amino Acid Sequence; AMPA receptory; Receptors, AMPA